Inequalities in the provision of sexual health information for young people. Issue 2 (1st April 2007) - Mclaughlin, Marian; Thompson, Kate; Parahoo, Kader; Armstrong, Janice; Hume, Allison
Abstract : Background: Sexual health has been emphasised in national and regional strategies as a target for health and social well-being. In Northern Ireland (NI), the Sexual Health Promotion Strategy concentrates on reducing the incidence of sexually transmitted infections (STIs), reducing the number of unplanned births to teenage mothers, providing appropriate, effective and equitable sexual health information, and facilitating access to sexual health services. This article reports on a study carried out within NI and explores young people's knowledge and sources of sexual health information. Methods: School pupils aged 14–18 years ( n = 414) participated in the study and a self-administered questionnaire was used to collect the data. Results: Whilst approximately half of the respondents reported being sexually active, only 68.2% always used some form of contraception. In fact, 40.8% of sexually active females had used the 'morning-after pill', with 37.5% of these respondents using this method more than once. The results also indicated that students receive varying amounts of sexual health information from schools resulting in inequalities with regard to sources of information. Students from a Roman Catholic religious background were more likely to receive information on sexual health from informal sources such as friends, books/magazines or television/radio than from within the school environment compared with their Protestant counterparts. Conclusions: The provision of standard and accurate information appropriate to the target population is necessary in order to reduce the increasing rates of STIs and help the Government reach their target of halving the teenage pregnancy rate by the year 2010.